Capital Theory, Crises, and Business Cycles: The Triangular Debate between Hayek, Keynes, and Sraffa - Kurz, Heinz D. (Journal of Reviews on Global Economics, 2015)
The paper discusses aspects of the triangular debate between Hayek, Keynes, and Sraffa on economic crises, business cycles and the role of capital theory in an analysis of these phenomena. It is argued that Sraffa was both critical of Hayek’s monetary overinvestment theory and Keynes’s use of the concept of commodity rates of interest Sraffa had employed in his criticism of Hayek and of Keynes’s theory of liquidity preference.